2019
DOI: 10.1016/j.irfa.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

What drives dividend smoothing? A meta regression analysis of the Lintner model

Abstract: This page was generated automatically upon download from the ETH Zurich Research Collection. For more information please consult the Terms of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 119 publications
1
27
1
Order By: Relevance
“…Accounting for this problem leads to a larger estimated speed of adjustment coefficient. Also, they provide a detailed literature review on the Lintner model; a meta-regression analysis can be found in Fernau and Hirsch (2019). These results are in line with a wide range of qualitative studies, see Powell (2009) for a summary.…”
Section: Related Literaturesupporting
confidence: 64%
“…Accounting for this problem leads to a larger estimated speed of adjustment coefficient. Also, they provide a detailed literature review on the Lintner model; a meta-regression analysis can be found in Fernau and Hirsch (2019). These results are in line with a wide range of qualitative studies, see Powell (2009) for a summary.…”
Section: Related Literaturesupporting
confidence: 64%
“…Therefore, including working papers in the MRA in some instances might not help to detect publication bias, while the inclusion of precision as an independent variable is more accurate (e.g. [82, 83]).…”
Section: Methodsmentioning
confidence: 99%
“…Existing applications in financial economics include the explanation of the heterogeneous results of the marginal tax effect on the corporate debt ratio (Feld et al, 2013), the market equity premium (van Ewijk et al, 2012), the efficient market hypothesis (Geyer-Klingeberg et al, 2018c;Kim et al, 2014), the determinants of corporate cash holdings (Weidemann, 2016), dividend smoothing (Fernau and Hirsch, 2017), the firm value effects of hedging (Geyer-Klingeberg et al, 2018a), and the determinants of corporate capital structure (Hang et al, 2018a, b).…”
Section: <<< Insert Table 1 About Here >>> 4 Methodologymentioning
confidence: 99%